PERAN PEMERINTAH DESA DALAM PENDATAAN PENDUDUK PENDATANG KAMPUNG PERAWANG BARAT - Johan Frengky; Tito Handoko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Migrant residents are residents who come as a result of relocation from outside the Siak Regency area to live permanently or temporarily, having fulfilled the stipulated conditions. In accordance with the data obtained which states that the West Perawang Village illustrates that the immigrant community in West Perawang Village who does not have a temporary permanent permit card, a certificate of moving from the place of origin while in Siak Regional Regulation No. 8 of 2002 Article 37 explains the Arrival of Citizens Indonesia caused by migration within or outside the Siak Regency area must be registered with the local lurah/village within a period of no later than 15 (fifteen) working days from the date of the moving certificate.            The purpose of this research is to implement the migrant population registration policy which is expected to provide a solution to overcome the problem of high immigrant population development in this area. It can be seen that the implementation of the migrant population registration policy is expected to provide a solution to overcome the problem of high immigrant population development in this area. Namely, the form of a registration policy for migrants to answer the problem of the fast migrant population in Perawang Barat village and the implementation of a registration policy is a real solution in overcoming the problem of migrants. Keywords: Role of Village Government, Immigrant Populatio